2021
DOI: 10.1002/ps.6627
|View full text |Cite|
|
Sign up to set email alerts
|

Transgenic Cry1Ac + CpTI cotton does not compromise parasitoid‐mediated biological control: An eight‐year case study

Abstract: BACKGROUND The on‐farm deployment of genetically modified crops may negatively affect nontarget arthropods, potentially disrupting food web structure and ecosystem functions. Aphid–parasitoid interactions are well‐suited to study these potential impacts in agro‐ecosystems. Over the span of 8 years, we systematically compared infestation levels of the aphid Aphis gossypii, its associated parasitoid community and overall parasitism rate between transgenic Cry1Ac + CpTI cotton and nontransgenic cotton. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Meanwhile, the mean temperature in 2022 was higher along the sampling months compared to the previous year, and with the elevation of temperature towards 40°C and above, the population of ladybirds diminished. Yang et al (2022) found that at temperatures above 35°C under laboratory conditions, the longevity of the mature insects of this species diminished compared to lower temperatures, which was in line with our eld observations. Developmental and life history investigations of ladybirds speci cally indicated that the body size, the length of their developmental period, and longevity would diminish with temperature elevation, though these changes are different depending on the species (Nedved and Honek 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, the mean temperature in 2022 was higher along the sampling months compared to the previous year, and with the elevation of temperature towards 40°C and above, the population of ladybirds diminished. Yang et al (2022) found that at temperatures above 35°C under laboratory conditions, the longevity of the mature insects of this species diminished compared to lower temperatures, which was in line with our eld observations. Developmental and life history investigations of ladybirds speci cally indicated that the body size, the length of their developmental period, and longevity would diminish with temperature elevation, though these changes are different depending on the species (Nedved and Honek 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Hippodamia variegata is a multivorous species with global distribution (Krafsur et al 1996;Gordon 1987;Franzman 2002). Since differences in the geographical distribution of ladybirds depend on the extent of tolerating heat and environmental changes of the species of this family of Coleoptera (Yang et al 2022), it seems that H. variegata is able to operate in a wide range of temperatures. Various factors affect the population trend of insects, including climatic changes (drought, severe precipitation, extreme temperature, and storm), degradation of the habitat, pollutants, insecticides and herbicides ( In investigating the population of H. variegata in 2021 and 2022, we observed that the maximum population of the species was found at 30 -35 °C thermal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, following an increasing density of live aphids, the predator showed an obvious preference for live aphids rather than mummies, but when there was a low prey density, there was no significant preference between live aphids and mummies (i.e., 10 mummies + 10 live aphids in the T2 treatment). Actually, the parasitism rate of aphids was relatively low (less than 10%) in a previous survey [ 25 ]. Therefore, the ladybeetles preyed primarily on live aphids as natural enemies, supplemented by IGP on mummies.…”
Section: Discussionmentioning
confidence: 99%